A model of the socio‐hydrologic dynamics in a semiarid catchment: Isolating feedbacks in the coupled human‐hydrology system. Issue 8 (19th August 2015) - Elshafei, Y.; Coletti, J. Z.; Sivapalan, M.; Hipsey, M. R.
Abstract The challenge of sustainable freshwater management requires identification and characterization of the underlying components and dynamic interactions within the coupled human‐hydrology system. This paper builds a model that captures the dynamic water balance evolution and coupled human response within the Lake Toolibin catchment in West Australia's wheatbelt region. Two subcatchments in different parts of the landscape were selected to examine the key emergent properties of the coupled socio‐hydrology system over a 100 year period, by analyzing the two‐way feedbacks of land use management (human system feedback) and land degradation (natural system feedback). Using a relatively simple parameterization of community sensitivity to land degradation within the model, we identified positive and negative feedbacks, the presence of threshold behavior, time scale differences between fast and slow moving variables, differences in time lags resulting from disparate resistance levels of the natural system, and the degree of adaptive learning inherent in the human system. Specifically, the valley floor subcatchment transitioned through four phases—expansion, contraction, recession, and recovery—demonstrating a threshold shift in the human feedback after 60 years, while the upslope subcatchment appears to still be in the contraction phase, with no sign of reaching a threshold shift in 100 years. These results demonstrate that the model is capable of isolating the two‐way feedbacks of the coupled system and has implications for resilience theory, suggesting that greater resistance in the underlying natural system counteracts the onset of a negative feedback loop and instigation of adaptive behaviors in the human system.